CASE REPORT OF IDIOPATHIC BILATERAL ORBITAL MYOSITIS - ÅžimÅŸek, Fatma (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Orbital myositis is an inflammatory disease affecting extraocular muscles. Mostly unilateral and rarely bilateral orbital involvement is seen. Bilateral involvement is a secondary table to systemic diseases and recurrence can be seen. Diagnosis is made by clinical, examination and imaging. Increased density of extraocular muscles and increased muscle mass should be seen in computed tomography or magnetic resonance imaging. The basis of the diagnosis is exclusion and the differential diagnosis needs to be done well. Steroids and other immunosuppressive agents may be used in the treatment. Patients respond dramatically to steroid treatment. While short-term steroid treatment may be sufficient in idiopathic patients, orbital myositis secondary to systemic disease requires longer-term and non-steroid immunosuppressive treatments. Here, a case of idiopathic orbital myositis with bilateral involvement is presented as it is a rare condition.Â